ORIGIN AND BIOGEOCHEMICAL CYCLING OF ORGANIC NITROGEN IN THE EASTERN ARCTIC OCEAN AS EVIDENT FROM D- AND L-AMINO ACIDS - Dittmar T.; Fitznar H.P.; Kattner G. (My University, 2001)
The chemical structure of organic nitrogen and the mechanisms of its cycling in the oceans still remain elemental questions in contemporary marine sciences. The Arctic Ocean provides a model system for studying the fate of terrigenous compounds in the ocean. We chemically characterised and traced the discharge of dissolved organic nitrogen (DON) and its particulate counterpart (PON) from the Russian rivers into the central Arctic Ocean. We focused on the d- and l-enantiomers of amino acids, the principal organic nitrogen compounds of living biomass. Total dissolved and particulate hydrolysable amino acids (TDAA, PAA) exhibited highest concentrations in the rivers (TDAA: 3.2 μM; PAA: 5.0 μM on average), contributing ∼40% to DON and ∼60% to PON. In the Arctic Ocean, TDAA and PAA decreased to concentrations of <1 μM, accounting only for ~10% of DON but ~80% of PON. Dominant amino acids in TDAA were glycine and alanine (in the rivers, 35% of TDAA; in deepwater, 49%), followed by aspartic acid, glutamic acid, and serine. Threonine was also abundant in the rivers, and leucine in deep seawater. Microbial-derived d-enantiomers of aspartic acid, glutamic acid, serine, and alanine were found in significant amounts in all river and seawater samples, both dissolved and suspended. In riverine TDAA d-aspartic acid was most abundant (21% of total aspartic acid); in deep seawater d-alanine predominated (44% of total alanine). The proportions of all d-enantiomers were significantly higher in oceanic versus riverine TDAA and increased with depth in the Arctic Ocean. PAA exhibited much lower proportions of d-enantiomers than TDAA (generally <0% of the respective amino acid).